Co-Pyrolysis Behavior, Kinetic and Mechanism of Waste-Printed Circuit Board with Biomass - Prajapati, Sonalben B.; Gautam, Alok; Gautam, Shina; Yao, Zhitong; Tesfaye, Fiseha; Lü, Xiaoshu (MDPI, 2023)
Waste-printed circuit boards (WPCBs) account for approximately 3–6 wt% of total electronic waste. Due to their content of thermosetting materials and added brominated fire retardants, their recycling and disposal is difficult and not eco-friendly. Pyrolysis as a thermal degradation process may assist in the solution of this problem. In addition, using biomass as an additive can upgrade the bio-oil and fix bromines in the char. In this study, cotton stalk (CS) is chosen as an additive and kinetic of the pyrolysis of three samples namely: PCB, CS, and CS:PCB (50:50) were investigated by the thermogravimetric analyzer (TGA) at heating rates of 5, 10, and 15 K/min. Three non-isothermal methods: FWO, KAS, and Starink were found in good agreement with the TGA data; however, the FWO method was more efficient in the description of the degradation mechanism of solid-state reactions. For CS and CS:PCB (50:50), α was increased from 0.2 to 0.9 with the FWO method, and calculated Eα values were found in the range of 121.43–151.88 and 151.60–105.67 kJ/mol in zone 1, while 197.06–79.22 and 115.90–275.06 kJ/mol in zone 2, respectively. Whereas, for PCB in zone 1, Eα values were found to be in the range of 190.23–93.88 kJ/mol. The possible decomposition mechanism was determined by the Criado method, which was in agreement with the mechanism model for reaction order n = 3. The oil product was also analyzed using Fourier-Transform Infrared Spectroscopy analysis.
Keywords: waste printed circuit board; electronic waste; cotton stalk; co-pyrolysis; kinetics; fi=Energiatekniikka|en=Energy Technology|